EFEKTIFITAS TERAPI MUSIK KLASIK TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU PRIMIPARA POST OPERASI SECTIO CAESAREA - Kevin A. P. Here (CHMK Applied Science Journal, 2018)
Sectio Caesarea is the way to give birth to the fetus by making an incision through the front wall of the uterus. Once the patient becomes aware, he will feel pain in the affected part of the body. Pain that is not handled properly will cause problems both physically and psychologically. Nonpharmacologic pain methods are usually chosen because they have a very low risk. One of the most effective distractions is music, which can reduce physiological pain, stress, and anxiety by diverting one's attention from pain. The purpose of this study to determine the effectiveness of classical music therapy to decrease the intensity of pain in primiparous mother with postoperative pain sectio caesarea surgery in the Flamboyan Room RSUD Prof. Dr. W. Z. Johannes Kupang. This research method is quasi-experimental, sample selection using accidental sampling. The sample in this study were 50 respondents divided into groups of intervention and control group each of 25 respondents. The study was conducted on 19 May to 19 June 2017 in Flamboyan Room of RSUD Prof. Dr. W. Z. Johannes Kupang. Data collection was done by giving classical music therapy then the researchers measure the scale of pre and post pain using the scale of pain McGill. The results showed that classical music therapy technique is effective in decreasing postoperative pain of cesarean section surgery as evidenced by the independent t-test where p value = (0.000) is smaller than α = 0,05 with mean pain reduction mean = 2.04. In conclusion, classical music therapy is effective to reduce postoperative pain sectio caesarea surgery in primiparous mother in Flamboyan room. Dr. W. Z. Johannes Kupang. Keywords: Pain, classical music, primipara